One Nation, One People draft (1964)
A draft of the 1964 Democratic Party platform titled "One Nation, One People," presented to the Democratic National Convention. It outlines the party's commitments to peace, strong national defense, civil rights, economic growth, and expanded opportunities in education, health care, and employment, while emphasizing unity following President Kennedy's assassination. The platform highlights foreign policy goals such as arms control, support for the United Nations and NATO, resistance to Communist expansion, and leadership in space exploration. Domestically, it promotes civil rights enforcement, anti-poverty initiatives, Social Security expansion, labor protections, agricultural support, urban development, and conservation of natural resources.